Risk Management in Born Globals: the Case of Brazilian Craft Breweries - Fabricio Stocker (FUCAPE Business School, 2019)
This work analyzes how risk management occurs in the internationalization process of Brazilian born global companies. Accordingly, we adopted the qualitative research approach, used a multiple case study strategy, and selected seven relevant craft breweries with national prominence. The findings highlight how risks are perceived in the internationalization process by managers and classified among commercial, intercultural, monetary and country risks. We also identified that these enterprises use different actions to mitigate risks, such as planning, market research, and building scenarios. The contributions discussed in this study are the identification of factors such as the international background of managers and the use of networks to minimize the perception of risk. Additionally, we discussed the ways in which risks are perceived and how the different mitigation strategies work. Finally, we proposed an integrated risk management model for the internationalization of born globals.